Insight into the buying behaviour of consumers for chilli in Indonesia: Households and food businesses in selected cities - Yanti Nuraeni Muflikh; Adhitya Marendra Kiloes (Applied Food Research, 2024)
In Indonesia, chilli are marketed mainly through traditional markets, where households are the primary consumers. Emerging food businesses and modern retailers provide market opportunities for farmers and develop chilli value chains. This study aims to understand the preferences and buying behaviors of households and business organizations regarding chilli. A total of 121 households and 47 business organizations were surveyed face-to-face, using a semi-structured questionnaire. The respondents were spread across Jakarta and surrounding urban areas. Descriptive statistical analysis, frequency distribution, cross-tabulation, and the Mann-Whitney U test, a nonparametric test to compare the preferences of the two consumer groups for chilli and product attributes, were performed. To complement the descriptive statistics, narrative descriptive analysis was employed to examine consumers' responses and reasons for the open-ended questions. The results show that households buy chilli weekly from nearby shops and food businesses daily from traditional markets, preferring them for lower prices and variety. Age positively correlates with purchase frequency, whereas household size correlates with both frequency and expense. Food business expenditure correlates with revenue and years of operation. The results also confirm that consumers exhibit similar preferences for most attributes but differ in their emphasis on freshness, peel smoothness, distance, and availability during the off-season. Indonesian consumers are concerned about chilli price volatility, freshness, and availability, which significantly impact purchasing decisions.